CONCEPTUAL FUNDAMENTALS OF PROVISION OF THE TRACK OF QUALITY EDUCATION (CHALLENGES OF TIME AND DEVELOPMENT STRATEGY) - Гаращук, Олена; Куценко, Віра; Kinash, Iryna Petrivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article deals with the role of continuous quality education in ensuring the socio-economic development of the country and in accelerating the relevant changes taking place in the country. It is noted that everyone’s life is connected with education and, above all, the improvement of their welfare. The authors of the study presented in this article consider the trends in the development of quality education in theoretical and practical aspects, the components of which are: scientific and theoretical foundations of achieving quality education; basic conceptual provisions for ensuring the competence of specialists; theoretically substantiated principles inherent in the relevant educational system. In this regard, the main functions performed by the educational sphere are revealed. Much attention in the article is paid to highlighting the essence of the category "quality of education". The ways and directions of achieving quality education and ensuring significant changes in educational activities, bringing it to a qualitatively new level of development, which should contribute to the achievement of positive qualitative changes in education are substantiated. It is emphasized that a significant role in achieving this belongs to the resource base and ways to improve it are considered. It emphasizes the need for active implementation in educational activities of projects that provide for the implementation of effective measures to provide educational institutions with modern material and technical base, the latest teaching aids to perform these institutions of their socially significant functions. Based on the understanding of the paramount importance of the mission of education, which is especially evident in our time, formed a new concept of education, which requires the introduction of new information technologies in the educational process, the formation of knowledge economy, transition to innovative economic growth, implementation of social partnership. humanism, social security, etc.